STRUCTURE OF HYDRATED ZN2+ AT THE RUTILE TIO2 (110)-AQUEOUS SOLUTION INTERFACE: COMPARISON OF X-RAY STANDING WAVE, X-RAY ABSORPTION SPECTROSCOPY, AND DENSITY FUNCTIONAL THEORY RESULTS - Zhang Z.; Fenter P.; Kelly S.D.; Catalano J.G.; Bandura A.V.; Kubicki J.D.; Sofo J.O.; Wesolowski D.J.; Machesky M.L.; Sturchio N.C.; Bedzyk M.J. (My University, 2006)
Adsorption of Zn2+ at the rutile TiO2 (110)-aqueous interface was studied with Bragg-reflection X-ray standing waves (XSW), polarization-dependent surface extended X-ray absorption fine structure (EXAFS) spectroscopy, and density functional theory (DFT) calculations to understand the interrelated issues of adsorption site, its occupancy, ion-oxygen coordination and hydrolysis. At pH 8, Zn2+ was found to adsorb as an inner-sphere complex at two different sites, i.e., monodentate above the bridging O site and bidentate between two neighboring terminal O sites. EXAFS results directly revealed a four or fivefold first shell coordination environment for adsorbed Zn2+ instead of the sixfold coordination found for aqueous species at this pH. DFT calculations confirmed the energetic stability of a lower coordination environment for the adsorbed species and revealed that the change to this coordination environment is correlated with the hydrolysis of adsorbed Zn2+. In addition, the derived adsorption locations and the occupancy factors of both sites from three methods agree well, with some quantitative discrepancies in the minor site location among the XSW, EXAFS, and DFT methods. Additional XSW measurements showed that the adsorption sites of Zn2+ were unchanged at pH 6. However, the Zn2+ partitioning between the two sites changed substantially, with an almost equal distribution between the two types of sites at pH 6 compared to predominantly monodentate occupation at pH 8.